(untitled) (Journal of Human Sciences, 2022)
during this scientific paper we address the theories of development critically, and this study acquires its importance through focusing on the criticisms that have been directed to the theories of development. this topic is considered as a new one, in which the research still needs more studies should be conducted. this paper is a scientific deals with the field of development, this topic was addressed through the following :- first: concepts. second: development theories. third: criticism of development theories. in this study the researcher used the descriptive method relying on the literature that dealt with the main subject of the study, it is an attempt to clarify different points of view, with the aim of reaching a theoretical scientific analysis. the current study relies on a critical analysis of the theories of development. it is considered as descriptive analytical studies. western theories failed to present theories capable of understanding the reality of development, which is to change the face, but its efforts were limited to parts of an attempt to reconcile and partially restore western theories, and these theories have lost the ability to understand or change reality, as well as the desired development of ideologically oriented theories, the development of backward societies, as well as theories in general failed to provide a clear picture of how the developed societies develop.